Biznes z terrorystami. Brudne interesy wywiadu wojskowego PRL z bliskowschodnimi organizacjami terrorystycznymi - Gasztold-Seń, Przemysław (Pamięć i Sprawiedliwość, 2014)
The declassification of the archives of the Polish Military Intelligence services (Zarząd II Sztabu Generalnego Wojska Polskiego) proved that this institution had maintained secret relations with some Middle Eastern terrorist organizations during the Cold War period. In my paper, I describe the ties between the Polish Military Intelligence, Abu Nidal’s Organization (ANO), and Monzer Al-Kassar’s group. Their mutual contacts were based on different agendas, among whose those linked to international politics and arms trade were of utmost importance. The members of ANO received scholarships to Polish universities, and could conduct business there. Their company – „S.A.S. Investments Trading Company” was located in Warsaw and was used by the Polish government as arms dealers. Thanks to good relations between ANO and chronologically: the regimes in Iraq, Syria and Libya, those dictatorships were interested in signing contracts to purchase Polish military equipment. ANO got commissions from executed contracts and it was one of their major profits, which later was spent on various terrorist purposes. The chief of ANO network in Poland – Samir Najmeddin – had very good relations with the Polish staff from the Central Engineering Board (Cenzin) – a state company responsible for export of Polish weapons and military advisors. This institution was secretly controlled by the Military Intelligence and Counterin- telligence services. ANO was also used as a provider of embargo goods for Polish secret services. That is why the members of Abu Nidal group were “untouchable” in Poland. Despite the fact that civilian services tried to put them under surveillance, the military services supported and protected terrorists. The relations with Monzer Al-Kassar’s group were based on economic grounds. During the 80s, he was one of the biggest arms dealers in the world. Together with Samir Najmeddin from ANO, they were the most important individual brokers for Cenzin. Kassar’s influence and connections with many Middle Eastern governments was so significant for the Polish government, that Cenzin established